Efektivitas Metode Finger Qur’an Dalam Meningkatkan Kualitas Hafalan Al-Qur’an - Batubara, Eka Elviana; Fauzi, Ahmad; Inzah, M. (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The background of this research arises from a gap in understanding and implementing the Finger Qur'an method, which is understood as one of the strategies to improve the quality of Quran memorization among students, especially at Darussalam Motivator Qur'an Islamic Boarding School in Probolinggo. Therefore, this research utilizes a qualitative approach through data collection techniques including observation, interviews, and documentation with the research goal of understanding the implementation model of Finger Qur'an in improving the quality of memorization among students in memorizing the Quran. The results of this study explain; Students show improvement in understanding makhorijul letters, applying tajweed, and fluency in recitation, The Finger Qur'an method is considered to have a significant impact on improving Quran memorization, The Finger Qur'an method becomes a prototype in improving Quran memorization.